Contemporary Issues In The Methodology Of Ethnological Research - Davlatova, Saodat Tilovberdievna (TLEP – International Journal of Multidiscipline, 2025)
This article examines contemporary issues in ethnological research methodology, reflecting global changes in the social and cultural spheres. It examines the evolution of methodological approaches, the use of qualitative and quantitative methods, the impact of technology, and ethical challenges. Particular attention is paid to the role of globalization, cross-cultural research, and the diversity of modern methodological approaches. The article discusses the challenges associated with adapting traditional methods to new conditions, as well as the importance of considering local and global contexts when studying cultures.